PRE-SERVICE TEACHERS' ATTITUDES TOWARD SOCIO-SCIENTIFIC ISSUES AND THEIR VIEWS ABOUT NUCLEAR POWER PLANTS - Kapici, Hasan Ozgur; Ilhan, Genc Osman (SCI METHODICAL CTR-SCI EDUCOLOGICA, 2016)
There is not a common attitude in a society for socio-scientific issues (SSI) such as whether to use nuclear power plants for energy production. Within this respect, the aim of the research is to examine pre-service science teachers' and pre-service social studies teachers' attitudes toward SSI and to reveal their views about setting up nuclear power plants in their country. The participant of research is 120 pre-service teachers. Firstly, Attitudes toward Socio-scientific Issues Scale (ATSIS) was implemented and then, focus group discussions were done with five students from each department separately so as to understand their views about nuclear power plants. Findings revealed that whereas pre-service teachers are eager to learn more about SSI, they have anxiety about it due to religion, moral and ethical perspectives. In addition, whereas both groups of pre-service teachers have some common views about nuclear power plants, pre-service science teachers do not have more positive views about having nuclear power plants in their country.
Keywords: attitude towards socio-scientific issues; focus group discussion; pre-service teachers; nuclear energy; SOCIOSCIENTIFIC ISSUES; DECISION-MAKING; KNOWLEDGE; DILEMMAS; Education & Educational Research